Conceptual Analysis of ’Windbreaks’ and ’Shelterbelts’ in Agroforestry - Ramanan, Suresh; S, Manojkumar; A, Arunachalam; A.K., Handa; V, Priyanka (Indian Journal of Agroforestry, 2023)
Understanding basic terminologies make a bigger difference in gaining knowledge. Windbreak(s) and/or shelterbelt(s) are old topics in agroforestry among other management systems. There has always been a debate on the difference between these two terms and these two terms are used by the researchers without any universal criteria. In order to point out the similarity, and differences of these terminologies - the research weaving approach was adopted following PRISMA guidelines and the results are presented here. As per the analysis, usage of one of these terminologies or both was found to be region/country-specific and currently, the windbreak term is mostly used by the scientific community. The analysis also revealed that there is no consistent pattern in usage of these terms among countries like China, the USA, Poland, Canada, Russia, New Zealand, etc. In the Indian context, these two terms were regarded as different, yet there is no scientific literature to prove the significant difference. This study concludes that the terms windbreak(s) and shelterbelt(s) can be used synonymously.